Paracetamol: a focus for the general pediatrician. - Marzuillo, Pierluigi; Guarino, Stefano; Barbi, Egidio (Eur J Pediatr, 2014)
UNLABELLED: Paracetamol (acetaminophen) is one of the most popular and widely used drugs for the treatment of pain and fever in children. This drug has multiple mechanisms of action, but its pharmacodynamic is still not well known. The central nervous system is the main site of action and it mirrors the paracetamol effect compartment. The recommended dosages and routes of administration should be different whether paracetamol is used for the treatment of pain or fever. For example, the rectal route, while being efficacious for the treatment of fever, should be avoided in pain management. Paracetamol is a safe drug, but some clinical conditions and concomitant drugs, which are frequent in clinical practice, may increase the risk of paracetamol toxicity. Therefore, it is important to optimize its administration to avoid overdoses and maximize its effect. The principal mediator of the paracetamol toxicity is the N-acetyl-p-benzo-quinone imine (NAPQI), a toxic product of the paracetamol metabolism, which could bind cysteine groups on proteins forming paracetamol-protein adduct in the liver. CONCLUSION: Although frequently prescribed, the concept of "effect compartment concentration" and the possible co-factors that could cause toxicity at recommended doses are not familiar to all pediatricians and general practitioners. We reviewed the literature concerning paracetamol mechanisms of action, we highlighted some relevant pharmacodynamic concepts for clinical practice, and we summarized the possible risk factors for toxicity at therapeutic dosages.
Keywords: Acetaminophen; Analgesics, Non-Narcotic; Child; Drug Overdose; Fever; Humans; Pain; Risk Factors